Effects of Chlorella vulgaris Supplementation on Performances of Lactating Nulliparous New Zealand White Rabbits Does and Their Kits - Sikiru, A. B.; Arangasamy, A.; Ijaiya A. T.; Ippala, J. R.; Bhatta, R. (International Journal of Livestock Research, 2019)
Thirty-five lactating New Zealand white rabbits were divided into five experimental groups (n = 7) each with equal number of kits (n = 5). Control group was not supplemented while treatment groups were supplemented with 200, 300, 400 and 500 mg Chlorella vulgaris biomass per kg body weight daily. Daily feed intakes, weekly body weight changes and body condition scores were recorded. Body conditions scores was 2.30±0.14 (p < 0.009), milk yield 1333±77.47 g (p < 0.001), litter weight at 21 days was 574.65±45.86 (p < 0.001) while feed intake was 97.45±1.91 (p < 0.48). We concluded from the results that supplementation of the microalgae improved performances of the lactating rabbits and their kits; hence, it was recommended for supplementation at 400 mg per kg body weight in lactating rabbits for promotion of improved performances in both the rabbit does as well as their kits.